Self-efficacy, self-silencing and coping with stress for teachers from the city of Pirot - Stanković Đorđević, Mirjana M.; Nedeljković, Jasmina J. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The starting point for this paper is Lazarus and Folkman’s (1984, 2004) transactional approach to coping with stress and it analyses the relations between self-efficacy, self-silencing and stress coping strategies among educators who are involved in children’s education and upbringing on various levels, from pre-school to secondary school teachers. The research included 185 educators from the city of Pirot who answered the following questionnaires: General Self-Efficacy Scale (GSE, Schwarzer and al, 1997), Silencing the Self Scale (Jack and Dill, 1992), Coping Inventory for Stressful Situations Scale (CISS, Endler and Parker, 1990). The basic assumption was that there was a statistically relevant correlation between the levels of self-efficacy and self-silencing and the strategies for coping with stress. A statistically relevant positive correlation between a high level of self-efficacy and problem-focused coping strategy was confirmed among the educators who took part in the research (r=0,373, p<0,01), as well as the correlation between a high level of general self-silencing and coping focused on emotions and avoidance (r=0,614, p<0,01 и r=0,293, p<0,01). When it comes to differences in the levels of self-efficacy, self-silencing and stress coping strategies between educators regarding the level of education they are involved in, a subsample of lower-grade elementary school teachers stands out. Self-silencing is, as a whole (but not statistically relevant) and particularly the subscale of externalized self-silencing more evident in lower-grade elementary school teachers (F=0,019, p<0,05), as well as emotion-focused coping (F=0,023; p<0,05). The results of the research imply the need to explore resources that would contribute to the encouragement of constructive coping strategies and the preservation and improvement of the mental health of educators, lower-grade elementary school teachers in particular, in the environment and conditions that are not presently very favourable to them.